Early Intervention in Unilateral Retinoblastoma: A 2-Year-Old’s Journey Through Enucleation and Evidence-Based Care - Imelda, Eva; Adev, Sarra Mutiara; Jannah, Siti Rain; Toshniwal, Nikhil (Indonesian Journal of Case Reports, 2025)
Retinoblastoma is a neoplasm that arises from the retina and is frequently observed in pediatric patients, with a high degree of morbidity, particularly in underdeveloped nations. The classification of this tumor is based on its spread (intraocular and extraocular) and location (unilateral, bilateral, trilateral, and quadrilateral). Unilateral retinoblastoma is the most prevalent form, accounting for 60–70% of cases. A 2-year-old female patient was brought to the Eye Clinic of the Pediatric and Strabismus Department of Dr. Zainoel Abidin Regional Hospital by her parents with a complaint of a white spot in the center of her left eye, accompanied by decreased visual acuity for 3 months. A subsequent examination, using ultrasound (USG), revealed a mass at the base of the retina, accompanied by calcification and infiltration into the vitreous. An orbital scan revealed intraocular calcification, exclusively in the left eye. The patient was diagnosed with unilateral leukocoria OS et causa retinoblastoma grade E. Subsequent treatment plans included OS enucleation and EUA (Examination Under Anesthesia) procedures. Following the EUA procedure, no mass was identified in the right eye. An anatomical pathology examination revealed no spread to the optic nerve; therefore, chemotherapy was not given.